Physical modeling of geoelectromagnetic variations of Antarctic peninsula region - Maksymchuk, V. Yu.; Kobzova, V. M.; Ladanivskyy, B. T.; Martyuk, P. K.; Goncharuk, L. T. (Ukrainian Antarctic Journal, 2008)
The method of analog physical modeling was applied to study conductivity structure of Antarctic Peninsula and adjusting regions. The 3D scale conductivity model of region from 51.4° W to 68.6° W and from 60°S to 67.2°S with factor 1:200000 was created in the electrolytic tank with dimension 5x5x0.7 m according to a bathymetry map. The model was excited by the varying homogeneous magnetic field in the frequency band 6.0 – 0.1 MHz that corresponds to 2200 – 130000 s band in natural conditions. The magnetotelluric and geomagnetic response functions was obtained at 12 points along profile across model of Antarctic Peninsula. 2D inversion of obtained response functions was compared with real geoelectric cross section which are reliable known for scale model. This comparison has allowed to estimate the influence of real 3D effects on geoelectric investigation in the region under study.